AKR1D1*36 C>T (rs1872930) allelic variant is associated with variability of the CYP2C9 genotype predicted pharmacokinetics of ibuprofen enantiomers – a pilot study in healthy volunteers - Kapedanovska Nestorovska Aleksandra; Jakjovski Krume; Naumovska Zorica; Sterjev Zoran; Geskovska Nadica Matevska; Mladenovska Kristina; Suturkova Ljubica; Dimovski Aleksandar (Acta Pharmaceutica)
The relative contribution of CYP2C9 allelic variants to the pharmacokinetics (PK) of ibuprofen (IBP) enantiomers has been studied extensively, but the potential clinical benefit of pharmacogenetically guided IBP treatment is not evident yet. The role of AKR1D1*36C>T (rs 1872930) allelic variant in interindividual variability of CYP450 mediated drug metabolism was recently elucidated. A total of 27 healthy male subjects, volunteers in IBP single-dose two-way cross-over bioequivalence studies were genotyped for CYP2C9*2, CYP2C9*3 and AKR1D1*36 polymorphisms. The correlation between CYP2C9 and AKR1D1 genetic profile and the PK parameters for S-(+) and R-(−)-IBP was evaluated. Remarkable changes in the PK values pointing to reduced CYP2C9 enzyme activity were detected only in the CYP2C9*2 allelic variant carriers. Statistically significant association between the AKR1D1*36 allele and the increased IBP metabolism (low AUC0-t and 0–∞, high Cltot and short tmax values for both enantiomers) was observed in subjects carrying the CYP2C9 *1/*3 or CYP2C9*1/*1 genotype. The clinical value of concomitant CYP2C9 and AKR1D1 genotyping has to be further verified.